Tinjauan Kebutuhan Air Irigasi Saluran Sekunder Taroang Daerah Irigasi Kelara - Iqbal, Muhammad Taufik; Faisal, Zulvyah (INTEK: Jurnal Penelitian, 2018)
The purpose of the research is the determinationof Irrigation water requirement based on primer datas collectingand analysis factors of land preparation, plant growth,determination of water loss due to percolation. Irrigation waterrequirement depends from various factors in the preparation ofthe land, plant growth, determination of water loss due topercolation, the determination of the replacement of water andrain layer effectively. The availability of irrigation water iscalculated based on discharge data retrieval on the TaroangSecondary channel. which then processed to obtain the finalresult of the availability of water in the channel. Results of thestudy shown that needs water to irrigate an area of secondarychannels Taroang covering an area of 2,140 Ha as much 39.11m3/s. While the availability of water that goes into the secondarychannel taroang where discharge a minimum of 0.12 m3/s and themaximum discharge of 0.31 m3/s.